Internationalization Of Capital And Productive Process: Critical Analysis - Andreff, W.; Deleplace, G.; Duboeuf, F.; Gillard, L.; González-Vigil, Fernando; Lespes, J.; Bardais, L. (Universidad del Pacífico, 1974)
This research deals with the way of analysing the logic of capital reproduction, as a social relationship, focused on its internationalization. It presents a critical analysis of the most important authors and the political implications of their theories. The goal is to analyze these theoretical approaches to understand them and to contribute to the study of capital reproduction.